Sono-hydrolysis of banana stem midrib using HY-zeolite from natural sand-based silica as a catalyst - Sumari Sumari; Aman Santoso; Muhammad Roy Asrori; Yana Fajar Prakasa; Dinar Rachmadika Baharintasari (Institute of Advanced Engineering and Science, 2022)
Banana stem midrib has the potential as a glucose source through catalytic hydrolysis assisted by ultrasonic (sono-hydrolysis). Besides, natural sand-based silica is the potential as raw material for zeolite synthesis. The purpose of the study was to do two things: i) characterize HY-zeolite made from natural sand-based silica and ii) determine whether HY-zeolite is effective for sono-hydrolysis of banana stem midrib. There was a total of four processes that were carried out, including i) the extraction of silica, ii) the synthesis of HY zeolite, iii) the hydrolysis process, and iv) the glucose content test. The results of the study were gained two things: i) The findings of X-ray fluorescence (XRF), X-ray diffraction (XRD), scanning electron microscopy (SEM), and Fourier transform infrared (FTIR) on HY-zeolite are 2.3 Si/Al, obtained 2 theta and d-spacing data similarities for HY-zeolite, and formed T-O-T, O-T-O (T=Si/Al), and Si-OH groups respectively; and ii) HY-zeolite with ultrasonic was effective for hydrolyzing cellulose into glucose at maximum temperature and time, 55 °C and 6 hours.